Video‐assisted thoracoscopic surgery for ectopic mediastinal parathyroid adenoma. Issue 6 (19th August 2019) - Isaacs, K. E.; Belete, S.; Miller, B. J.; Di Marco, A. N.; Kirby, S.; Barwick, T.; Tolley, N. S.; Anderson, J. R.; Palazzo, F. F.
Abstract : Background: Primary hyperparathyroidism (PHPT), caused by an ectopic mediastinal parathyroid adenoma, is uncommon. In the past, when the adenoma was not accessible from the neck, median sternotomy was advocated for safe and successful parathyroidectomy. Video‐assisted thoracoscopic surgical (VATS) parathyroidectomy represents a modern alternative approach to this problem. Methods: Information on patients undergoing VATS was obtained from a specific database, including clinical presentation, biochemistry, preoperative imaging, surgical approach and patient outcomes. A comprehensive literature review was undertaken to draw comparisons with other publications. Results: Over a 2‐year period, nine patients underwent VATS parathyroidectomy for sporadic PHPT. Five patients had persistent PHPT following previous unsuccessful parathyroidectomy via cervicotomy, and four had had no previous parathyroid surgery. The median duration of surgery was 90 (range 60–160) min. Eight patients were cured biochemically, with no major complications. One patient required conversion to a median sternotomy for removal of a thymoma that had resulted in false‐positive preoperative imaging. Conclusion: With appropriate preoperative imaging, multidisciplinary input and expertise, VATS parathyroidectomy is an effective, safe and well tolerated approach to ectopic mediastinal parathyroid adenoma. Abstract : The authors' unit recently adopted a thoracoscopic approach to mediastinal parathyroidectomy. Unit data for their case series of thoracoscopic parathyroidectomies are reviewed here, including preoperative workup and operative findings. Recommended approach to mediastinal adenomas Abstract : Antecedentes: El hiperparatiroidismo primario ( primary hyperparathyroidism, pHPT) causado por un adenoma paratiroideo ectópico mediastínico es infrecuente. Hace años, cuando un adenoma no era accesible por vía cervical se propugnaba una esternotomía media para efectuar una paratiroidectomía segura y con éxito. La paratiroidectomía por cirugía toracoscópica asistida por video ( video‐assisted thoracoscopic surgical, VATS) es una alternativa moderna para el abordaje de esta patología. Métodos: La información de los pacientes tratados con VATS se obtuvo de una base de datos específica, incluyendo presentación clínica, bioquímica, radiología preoperatoria, abordaje quirúrgico y resultados de los pacientes. Se efectuó una revisión extensa de la literatura para efectuar comparaciones con otras publicaciones. Resultados: Durante un periodo de 2 años, 9 pacientes fueron tratados mediante paratiroidectomía por VATS debido a un pHPT esporádico, de los cuales 5 presentaban pHPT persistente después del fracaso de una paratiroidectomía por cervicotomía, mientras que los 4 restantes no habían sido operados previamente de cirugía paratiroidea. El tiempo medio operatorio fue de 101 minutos (rango 60‐160). Ocho pacientes se curaron bioquímicamente, sin ninguna complicación mayor. Un paciente precisó conversión a una esternotomía media para extirpar un timoma que había sido un falso positivo en la radiología preoperatoria. Conclusión: La paratiroidectomía por VATS es una intervención efectiva, segura y bien tolerada para la extirpación de un adenoma ectópico mediastínico, siempre y cuando se disponga de radiología preoperatoria adecuada, equipo multidisciplinar y experiencia.